2012
DOI: 10.1111/j.1442-200x.2012.03567.x
|View full text |Cite
|
Sign up to set email alerts
|

Tracheal colonization in preterm infants supported with nasal continuous positive airway pressure

Abstract: The trachea of premature infants supported with CPAP is at risk for bacterial colonization. Predisposing factors, mechanisms and clinical implications of these novel findings need to be studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…3,6,7 The predominant type of growth varies; gram negative bacilli are as frequent as gram positive organisms. [7][8][9][10] The aetiology of neonatal CLD, also known as bronchopulmonary dysplasia (BPD), is multifactorial and includes ventilator associated lung injury, inflammation and infection. [11][12][13][14][15][16] Infants who are mechanically ventilated for prolonged periods are at higher risk of developing CLD.…”
Section: What This Paper Addsmentioning
confidence: 99%
See 1 more Smart Citation
“…3,6,7 The predominant type of growth varies; gram negative bacilli are as frequent as gram positive organisms. [7][8][9][10] The aetiology of neonatal CLD, also known as bronchopulmonary dysplasia (BPD), is multifactorial and includes ventilator associated lung injury, inflammation and infection. [11][12][13][14][15][16] Infants who are mechanically ventilated for prolonged periods are at higher risk of developing CLD.…”
Section: What This Paper Addsmentioning
confidence: 99%
“…A longer duration of intubation increases the likelihood of bacterial colonisation 3,6,7 . The predominant type of growth varies; gram negative bacilli are as frequent as gram positive organisms 7–10 …”
mentioning
confidence: 99%
“…Results of this study are limited by the fact that it remains unclear whether the bacteria from positive catheter tips had already colonized the trachea [8] or whether colonization took place during catheter removal, which would then not involve a risk of transmission. This would have required an additional intratracheal smear before implementation of the LISAcatheter, which was regarded too invasive.…”
Section: Discussionmentioning
confidence: 95%
“…Teig et al 25 reported a decrease in incidence of nosocomial sepsis and attributed it to decreased tracheal bacterial colonization associated with LISA technique 81 …”
Section: Short‐term Outcomesmentioning
confidence: 99%